A Model Of Entrepreneurial Intentions Within The Persons With Disabilities Population - Baldridge,David; Dibrell,Clay; Neubaum,Donald (Frontiers of Entrepreneurship Research, 2008)
While self-employment presents many challenges, an entrepreneurial path for a person with a disability can mean the difference between unemployment or severe underemployment and a truly exceptional and prosperous career. Recent research highlights the importance of entrepreneurial intentions (i.e., the interest of a person in starting, acquiring or buying a business) as a precursor to entrepreneurial behavior (Zhao et al., 2005). Further, entrepreneurial self-efficacy (Zhao et al., 2005), defined as the level of confidence individuals have to identify new opportunities, create products, think creatively, or commercialize an idea, is positively associated with entrepreneurial intention. In reviewing the literature on people with disabilities, however, we find reason to believe that this model does not fully explain the entrepreneurial activities of persons with disabilities. Thus, we integrate the literatures on entrepreneurship and people with disabilities to propose a refined model. A few of the propositions offered by our model are included below.
Keywords: Management; Strategy & Entrepreneurship